Past, Present and Future of the Management of Plague Vertebrates in Costa Rica - Monge, Javier (2017)
The vertebrate pest affects the interests of the people in urban and agricultural environments, which has taken place since ancient times. In Costa Rica, information documented on this subject dates back more than one century. From the year 1911, with the appearance of the Boletín de Fomento (Development Bulletin), began references of the subject. In a first stage, 1910 – 1980, it is published in various sources about the problems generated by some vertebrates, among which stands out for its frequency the pocket gopher. Of these rodents, mention is made to the damage they cause, and some options are offered to control them with the use of poisons, traps, alterations of their habitat and biological control. The second stage, covering the period from 1980 to the present, is characterized by a more academic work on the subject, with more diversity of vertebrate involved. This stage gives special importance to bioecological aspects, as well as the characterization of damage. During this period stands out the contribution of the National University and later of the University of Costa Rica, with the integration of research, extension, or social action and the teaching of the subject of the vertebrate pest. As future prospect in this field, it is considered convenient the continuation of studies focused on bioecological aspects, since they underlie the actions of management. At the same time, further efforts are needed to aimed at the management of problem situations where participating vertebrate pest is evident.